The influence of destination image on domestic tourists' intention to return to bl. garden of Tabanan regency - Suprapto, I Nyoman Arto; Putri, Redita Octaviani (YAYASAN MITRA PERSADA NUSANTARA, 2023)
The Blooms Garden is a tourist destination in Tabanan which utilizes artificial photo spots tourist attractions as its tourism product. The number of visits by domestic tourists to The Blooms Garden is very large compared to foreign tourists due to the interest of local tourist who loves taking photo/selfie in the new and unique place. During their visits will provide various kinds of perceptions of the destination image towards The Blooms Garden. This study aims to determine the effect of destination image on domestic tourists' intention to return to The Blooms Garden, Tabanan. The method used in this study is a quantitative research method with a purposive sampling technique. Collecting data used questionnaire instrument distributed to 100 respondents by google form. The analysis technique used are instrument data testing (validity and reliability test), descripttive statistical analysis, simple linear regression analysis, coefficient of determination and t-test. The results of this study indicate that destination image has a significant effect on intention to return through the calculation of the t test analysis and produces a t-count > t-table = 8.812 > 1.66 at a significance of 5%.